Solution-processed colloidal quantum dot/organic hybrid tandem photovoltaic devices with 8.3% efficiency. (January 2017) - Aqoma, Havid; Azmi, Randi; Oh, Seung-Hwan; Jang, Sung-Yeon
Abstract: High-efficiency colloidal quantum dot (CQD)/organic hybrid tandem photovoltaic devices (HT-PVs) are developed through a low-temperature solution process. PbS-CQDs and blends of PTB7-Th/PC71 BM are used as the active materials for front- and back-cells, respectively. The effective series connection of the two heterogeneous sub-cells is successfully achieved using MoOx/Au/ZnO-based intermediate recombination layers (IMLs). By fine-tuning the current densities in the sub-cells and optimizing the IMLs by balancing the optical and electrical properties, HT-PVs with power conversion efficiency (PCE) of 8.27% ( V OC of 1.27 V, J SC of 10.36 mA cm −2, and FF of 0.63) are achieved. Furthermore, the fabrication of HT-PVs is achievable in ambient atmospheric conditions without thermal annealing that have comparable PCE (7.64%). The PCEs exhibited by these HT-PVs are thus far the highest values reported for CQD-based tandem photovoltaic devices. Graphical abstract: Highlights: Record efficiency (8.3%) for quantum dot/organic hybrid tandem photovoltaic devices. Successful current matching of the two sub-cells with absorption overlap. Development of efficient intermediate layers for hybrid tandem photovoltaic devices. High efficiency (7.6%) quantum dot/organic hybrid tandem photovoltaic devices by room-temperature annealing-free fabrication process.